ANALISIS URAIAN JABATAN PT. PLN (PERSERO) UIP3B SULAWESI - Dzar Fahiemah El Faiqah; Fanny Erdaningsih; Ghina Maharani M; Ismarli Muis (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
PT. PLN (Persero) UIP3B Sulawesi has carried out an organizational transformation this year, one of which is by making changes to its organizational structure so that an analysis is needed to prepare new job descriptions. The purpose of this job description analysis is to review and update the previous job descriptions in order to clarify the job descriptions for new divisions and positions at UIP3B Sulawesi. The benefit of preparing job descriptions is to clarify the job description or main tasks and functions of work units for each job designation, as well as to identify the competency requirements required for each job designation. This research approach is action research using Participatory Action Research (PAR) techniques through qualitative descriptive analysis. The results of this study are the latest job description forms that have changes to organizational structure, competency levels, business streams, and main tasks at each functional level to become more detailed and specific and relevant to the conditions of employees and the company.